The AU-EU Partnership and the COVID-19 Pandemic: Moving towards health sovereignty in Africa? - Philip J. Havik (Cadernos de Estudos Africanos)
The 6th AU-EU Summit presented a joint vision for a renewed inter-regional partnership with a strong emphasis on public health. With the COVID-19 pandemic as its backdrop, a common health agenda was agreed which pledged support for Africa’s fully-fledged health sovereignty. Different packages contemplated technical assistance and funding for improving health governance, infrastructures, human resources, health information and regulation, whilst ensuring vaccine dose sharing. This article looks at EU’s inter-regional health diplomacy and its ambition to shape African institutions, and the African Medicines Agency in particular. It addresses strategic considerations, comparing EU and AU models, regulatory policies, and their implementation, while considering the broader implications for African health sovereignty.